At What Age And How To Learn Computer Science? (based on analysis of foreign sources) - Najmiddinova Xilola Yokubjanovna (International Journal of Medical Toxicology and Legal Medicine, 2024)
As the digital technologies are becoming a main part of our lives, they are rapidly changing the way of life, living conditions and outlook of humanity to a completely new level. The wide range of digital technologies and their use not only in daily activities, but also in various fields of production, is bringing humanity to the fourth industrial revolution. This industrial revolution, based on the digital revolution, means a transition to fully automated production controlled by intelligent systems.